Dynamics of a "low‐enrichment high‐retention" upwelling center over the southern Senegal shelf. Issue 10 (29th May 2017) - Ndoye, Siny; Capet, Xavier; Estrade, Philippe; Sow, Bamol; Machu, Eric; Brochier, Timothée; Döring, Julian; Brehmer, Patrice
Abstract: Senegal is the southern tip of the Canary upwelling system. Its coastal ocean hosts an upwelling center which shapes sea surface temperatures between latitudes 12° and 15°N. Near this latter latitude, the Cape Verde headland and a sudden change in shelf cross‐shore profile are major sources of heterogeneity in the southern Senegal upwelling sector (SSUS). SSUS dynamics is investigated by means of Regional Ocean Modeling System simulations. Configuration realism and resolution (Δ x ≈ 2 km) are sufficient to reproduce the SSUS frontal system. Our main focus is on the 3‐D upwelling circulation which turns out to be profoundly different from 2‐D theory: cold water injection onto the shelf and upwelling are strongly concentrated within a few tens of kilometers south of Cape Verde and largely arise from flow divergence in the alongshore direction; a significant fraction of the upwelled waters are retained nearshore over long distances while travelling southward under the influence of northerly winds. Another source of complexity, regional‐scale alongshore pressure gradients, also contributes to the overall retention of upwelled waters over the shelf. Varying the degree of realism of atmospheric and oceanic forcings does not appreciably change these conclusions. This study sheds light on the dynamics and circulation underlying the recurrent sea surface temperature pattern observed during the upwelling season and offers new perspectives on the connections between the SSUS physical environment and its ecosystems. It also casts doubt on the validity of upwelling intensity estimations based on simple Ekman upwelling indices at such local scales. Key Points: Upwelling dynamics over the southern Senegal shelf strongly differs from 2‐D Ekman theory Overall upwelling intensity is only 15‐40% of the Ekman transport High retention over the southern Senegal shelf favors small pelagic fish reproduction